Forecasting Sales of Premium Oil Fuel, Pertalite, Pertamax, Pertamax Turbo and Bio Solar Using the Method Exponential Moving Average (EMA) (case Study: Klampis Gas Station Surabaya) - M Mahaputra Putra; Rahmawati Febrifyaning Tias; Ayu Dwi Safitri (JEECS (Journal of Electrical Engineering and Computer Sciences), 2020)
Along with the development and progress of current technology, fuel oil is one of the basic needs for both industry and transportation, demands will this fuel service becomes very important, and pertamina as the material provider fuel oil, must be able to guarantee the availability and smoothness of fuel products oil. The purpose of this study is to predict the amount of premium sales, pertalite, bio solar, Pertamax, and Pertamax turbo at Klampis Surabaya gas station for 2018 by using the forecasting method Exponential Moving Average ( EMA). Based on the results data processing carried out it can be concluded that the forecasting method that period 30 days are more accurate in predicting Premium, Pertalite, and Bio Solar 2018. And the 365 day period more accurate in predicting Pertamax, and Pertamax Turbo. Based on comparison of values MSE with MAPE, it can be concluded that using the MSE method to find values more good errors in this study. Based on the comparison of MSE values with MAPE, it can be concluded that using the MSE method to find better error valuesin this research.